Erythrocyte Sedimentation Rate for Assisted Diagnosis of Pediatric Osteomyelitis: A Meta-Analysis - Qi H; Zhu Z; Zhu D (Dove Medical Press, 2023)
Han Qi,1 Zhitao Zhu,2 Dongsheng Zhu3 1Department of Emergency Surgery, The Second People's Hospital of Lianyungang, Lianyungang, People's Republic of China; 2Department of Radiology, The Second People's Hospital of Lianyungang, Lianyungang, People's Republic of China; 3Department of Pediatric Orthopedics, The First People's Hospital of Lianyungang, Lianyungang, People's Republic of ChinaCorrespondence: Dongsheng Zhu, Department of Pediatric Orthopedics, The First People's Hospital of Lianyungang, Lianyungang, 222000, People's Republic of China, Email zhudongsheng@tmu.edu.cnObjective: For the diagnosis of pediatric osteomyelitis, the sensitivity, specificity, and predictive value of erythrocyte sedimentation rate (ESR) were evaluated in this study.Methods: A systematic computer-based search was performed for relevant articles focusing on the ESR diagnosis of pediatric osteomyelitis in PubMed, Embase, and the Cochrane Library with an inclusion criteria: 1) the diagnostic utility of ESR for diagnosing osteomyelitis patients under the age of 18;2) two-by-two contingency tables can be obtained. Case reports, review papers, and animal experiments were excluded.Results: The diagnostic meta-analysis included 8 studies involving 348 children with osteomyelitis, all of whom were tested for ESR. Diagnostic meta-analysis revealed a sensitivity and specificity of 0.90, 95% confidence interval (CI) (0.86- 0.93), and 0.50 (95% CI,0.47- 0.54) for ESR in pediatric osteomyelitis diagnosis, respectively. The positive likelihood ratio (LR), negative LR, and diagnostic odds ratio were 1.38,(95% CI,1.08- 1.78), 0.46, (95% CI,0.26- 0.73), and 3.20, (95% CI,1.33- 7.69), respectively. The area under the curve (AUC) was determined to be 0.80 based on the summary receiver operating characteristic curve (SROC).Conclusion: The literature on the use of ESR in pediatric osteomyelitis diagnosis was thoroughly reviewed in this study. It was also found that ESR may be useful as a biomarker for pediatric osteomyelitis diagnosis. Due to its low specificity, it should be used in combination with other markers such as C-reactive protein, neutrophil percentage, and white blood cell count.Keywords: osteomyelitis, pediatric, ESR, diagnosis, meta-analysis